(untitled) (Scientific journal of the Fergana State University, 2025)
It is difficult to find a formula for measuring the value of any cultural landscape created in fiction, since each author describes the territory based on his perception. An artistic landscape arises as a result of the intersection of the author’s artistic links with the elements of space. An artistic landscape is a mental perception that is formed within the framework of the subject’s cognition of literature in a process involving memory and materiality. The article is devoted to the analysis of the text of the landscape with the description of the village of Nigor in Alisher Navoi’s epic “Saddi Iskandari”, in which the processes of perception between the author and the recipient are linguocognitively investigated.